Indoor fungi on damp walls of buildings and their management - Shafa, Shabnam; Shamsi, S; Bashar, MA (Dhaka University Journal of Biological Sciences, 2014)
A total of eight species of fungi and one sterile fungus were isolated from the indoor damp walls. The fungi were Aspergillus flavus Link, A. fumigatus Fresenius, A. niger van Teighem, A. niger (culture type 1), A. terreus Thom, A. terreus (culture type 1), A. ustus, Fusarium sp., Penicillium sp. Ulocladium sp. and a fungus with sterile mycelia. The frequency percentage of association of A. fluvus, A. fumigatus and A. niger was higher than any other fungi. This is the first report of association of fungi in indoor damp walls from the Department of Botany, University of Dhaka and a private house of Dhaka city. Effects of six fungicides were evaluated against the isolated fungi. Bavistin and tall were found most effective against the radial growth of the damp wall fungi. DOI: http://dx.doi.org/10.3329/dujbs.v23i1.19821 Dhaka Univ. J. Biol. Sci. 23(1): 9-16, 2014